ANALISIS PRODUKTIVITAS AYAM JANTAN LAYER HASIL SUBTITUSI TEPUNG MAGGOT DAN JAGUNG : ANALYSIS OF PRODUCTIVITY OF CHICKENS MALE LAYER RESULTING FROM SUBSTITUTION OF MAGGOT FLOUR AND CORN - widayat, moch widayat; Mudawamah; Inggit Kentjonowaty (UNIVERSITAS ISLAM LAMONGAN, 2025)
The purpose of this study was to analyze the productivity of layer roosters related to feed consumption, body weight gain (PBB), feed conversion ratio (FCR), carcass weight and income over feed cost (IOFC). The materials used in this study were finisher phase layer roosters (aged 22 days to 60 days). The method used was experimental method using Randomized Block Design ( RBD ) with 4 treatments and 4 groups, each group consisted of 9 chickens and the total sample used was 144 finisher phase layer roosters (22 days old). The treatments given were P1 = 100% commercial feed, P2 = 80% commercial feed plus 20% BSF (Black Soldier Fly) maggot flour and corn, P3 = 70% commercial feed plus 30% BSF (Black Soldier Fly) maggot flour and corn, P4 = 60% commercial feed plus 40% BSF (Black Soldier Fly) maggot flour and corn. The results showed that the use of maggot BSF (Black Soldier Fly) flour substitution feed and corn had a very significant effect (P<0.01) on feed consumption and income over feed cost (IOFC), but did not show a significant effect (P>0.05) on body weight gain, feed conversion ratio, and carcass weight. The conclusion of this research is that substitution feed meal maggot BSF (Black Soldier Fly) and corn can increase the productivity of layer roosters seen from the amount of feed consumption decreased by 6.6% to 8.4% followed by an increase in income over feed cost by 19.11% to 34.28%. The suggestion of this research is the use of maggot BSF (Black Soldier Fly) and corn substitution feed can be used up to 40% with 60% commercial feed